The Implementation of Hypnoteaching Method in Improving Students’ Reading Comprehension - Abdullah Syukur; Ardhy Supraba (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The objective of this research is to find out the implementation of Hypnoteaching method in improving students reading comprehension. The researcher applied quasi-experimental design. The population of this research is the second semester students of Informatics Study Program at Cokroaminoto Palopo in 2022/2023 academic year. The researcher used cluster random sampling technique, where two classes were taken randomly as sample. The sample consists of 27 students of experimental class and 27 students of control class. There were two variables in this research, namely the implementation of Hypnoteaching method as independent variable and the students reading comprehension as dependent variable. The data was collected through reading test administered in pretest and posttest of each class. The result of data analysis shows that t-test value is greater than t-table value (5.34 > 2.056) at level of significance (p) = 0.05 with degree of freedom (df) = 26. It means that there is a significant difference of reading comprehension between two classes and it indicates that null hypothesis (H0) is rejected and alternative hypothesis (H1) is accepted. Therefore, based on the findings and discussion of this research, it can be concluded that the implementation of Hypnoteaching method improves students reading comprehension